Black locus (Robinia pseudoacacia L.) and Honey locust (Gleditsia triacanthos L.): technological aspects in relation with the use in solid wood products - Keil, Gabriel; Spavento, Eleana; Murace, Mónica; Millanes, Ana (Forest Systems, 2011)
<span style="line-height: 107%; font-family: ’TimesNewRomanPS’,serif; font-size: 10pt; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-ansi-language: ES; mso-bidi-font-family: TimesNewRomanPS; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;"><span style="line-height: 107%; font-family: ’TimesNewRomanPS-Italic’,serif; font-size: 12pt; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-ansi-language: ES; mso-bidi-font-family: TimesNewRomanPS-Italic; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;">Robinia pseudoacacia <span style="line-height: 107%; font-family: ’TimesNewRomanPS’,serif; font-size: 12pt; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-ansi-language: ES; mso-bidi-font-family: TimesNewRomanPS; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;">L. and <span style="line-height: 107%; font-family: ’TimesNewRomanPS-Italic’,serif; font-size: 12pt; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-ansi-language: ES; mso-bidi-font-family: TimesNewRomanPS-Italic; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;">Gleditsia triacanthos <span style="line-height: 107%; font-family: ’TimesNewRomanPS’,serif; font-size: 12pt; mso-fareast-language: EN-US; mso-fareast-font-family: Calibri; mso-ansi-language: ES; mso-bidi-font-family: TimesNewRomanPS; mso-bidi-language: AR-SA; mso-fareast-theme-font: minor-latin;">L, are tree species from USA and both was introduced in Europe. In the province of Buenos Aires, Argentina, plantations of these species are scattered, whose wood hasn’t been characterized technologically by standardized tests. The objetive of this job was to characterize technologically Black locus and Honey locust woods, both implanted in the province of Buenos Aires for its inclusion in the timber market. The physical and mechanical properties determined were: content humidity, apparent densities, dimensional changes, Janka hardness, static bending, cut parallel to fibers, compression perpendicular and parallel to fibers. Natural durability was estimated. Black locus and Honey locust woods were medium density and medium stability, hard, resistant to the cut and the compression perpendicular to fibers and showed values medium to low in parameters of static bending and compression parallel to fibers, values to take into account when designing structural elements. Black locus was the most resistant to fungal degradation. Both woods can be considered suitable for high-value uses in the construction and furniture industries (interior and exterior).